Transition‐Metal‐Free Tunable Chemoselective N Functionalization of Indoles with Ynamides1. Issue 32 (24th June 2014) - Hentz, Alexandre; Retailleau, Pascal; Gandon, Vincent; Cariou, Kevin; Dodd, Robert H.
Abstract Two unprecedented N functionalizations of indoles with ynamides are described. By varying the electron‐withdrawing group on the ynamide nitrogen atom, either Z‐indolo‐etheneamides or indolo‐amidines can be selectively obtained under the same metal‐free reaction conditions. The scope and synthetic potential of these reactions, as well as some mechanistic insights provided by DFT calculations, are reported.